Improving Clean and Healthy Living Behavior Through Education for Students of State Elementary School 096125 Tobasari: Peningkatan Perilaku Hidup Bersih dan Sehat Melalui Edukasi Pada Siswa SDN 096125 Tobasari - Petra Saragih, Nurlela; Laora Silitonga, Lisbeth; Rospitaria Tarigan, Almina; Isranil Laily, Eka; Sartika Munthe, Dewi; Sarah Jufrida Saragih, Ruth; Sari Siregar, Patimah; Rinawati, Rinawati; Nainggolan, Elfrida (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Clean and Healthy Living Behavior (PHBS) is a behavior formed by learning that enables a person or family to help themselves in terms of health and actively participate in improving the health of their community. To reduce health financing, PHBS is one of the main pillars of Healthy Indonesia. One important component in the process of Human Resources (HR) development is health, which includes education. In Indonesia, formal education starts at the Primary School (SD) level, with an emphasis on children aged six to twelve, which is an age vulnerable to disease. Promoting healthy lifestyles among students is crucial given the importance of health for the growth of human capital, the nature of primary school-age children, and how behavior affects health. It is imperative to encourage primary school students to lead a healthy lifestyle due to the fact that health is essential for the growth of human capital, the nature of primary school-age children, and how behavior affects their health. This community service uses a hands-on approach that allows for quick action. To achieve the goal, the Clean and Healthy Living Behavior (PHBS) program is used to increase the awareness of teachers and students. The methods used included instruction, mentoring, counseling, and self-practice of PHBS as well as provision of basic facilities. The results included increased knowledge of teachers and students of SD Negeri 096125 Tobasari about PHBS, daily application of PHBS values, and availability of public trash bins.